Water scarcity assessments in the past, present, and future - Liu, Junguo; Yang, Hong; Gosling, Simon N.; Kummu, Matti; Flörke, Martina; Pfister, Stephan; Hanasaki, Naota; Wada, Yoshihide; Zhang, Xinxin; Zheng, Chunmiao; Alcamo, Joseph; Oki, Taikan (Earth's future, 2017)
Water scarcity has become a major constraint to socio‐economic development and a threat to livelihood in increasing parts of the world. Since the late 1980s, water scarcity research has attracted much political and public attention. We here review a variety of indicators that have been developed to capture different characteristics of water scarcity. Population, water availability, and water use are the key elements of these indicators. Most of the progress made in the last few decades has been on the quantification of water availability and use by applying spatially explicit models. However, challenges remain on appropriate incorporation of green water (soil moisture), water quality, environmental flow requirements, globalization, and virtual water trade in water scarcity assessment. Meanwhile, inter‐ and intra‐annual variability of water availability and use also calls for assessing the temporal dimension of water scarcity. It requires concerted efforts of hydrologists, economists, social scientists, and environmental scientists to develop integrated approaches to capture the multi‐faceted nature of water scarcity. Key Points We provide a comprehensive review of water scarcity indicators and reflect on their relevance in a rapidly changing world There is a need to incorporate green water, water quality, and environmental flow requirements in water scarcity assessment Integrated approaches are required to capture the multi‐faceted nature of water scarcity